2022
DOI: 10.3390/cancers14164028
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy for Hepatocellular Carcinoma: Old and New Opportunities

Abstract: Hepatocellular carcinoma (HCC) is the most frequent primitive cancer of the liver, accounting for 90% of all recorded cases. HCC is the third most common cause of cancer-related death, with a 5-year survival rate of just 3%. In the advanced stages, systemic treatments allow doctors to obtain clinical benefits, although the prognosis remains very poor. In the past few decades, new molecular targeted therapies against receptor tyrosine kinases have been developed and clinically evaluated. Sorafenib was the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 152 publications
(200 reference statements)
0
34
0
2
Order By: Relevance
“…It is well known that the immune system plays an important role in controlling cancer progression. Recent year, immunotherapy has developed as the new first-line treatment option for advanced HCC [ 4 , 21 , 22 ]. Previous study indicated that tumor immune cell infiltration generates an immunosuppressive TME and presences a generally correlations with a worse prognosis [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the immune system plays an important role in controlling cancer progression. Recent year, immunotherapy has developed as the new first-line treatment option for advanced HCC [ 4 , 21 , 22 ]. Previous study indicated that tumor immune cell infiltration generates an immunosuppressive TME and presences a generally correlations with a worse prognosis [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is the sixth most commonly diagnosed malignancy and the third leading cause of cancer-related mortality worldwide [ 2 , 3 ]. In the past few decades, new therapeutic strategy, such as molecular targeted therapies and immunotherapy, have been developed and clinically evaluated with interesting results in HCC [ 4 ]. Remarkably, the combination of immune checkpoint inhibitors and VEGF inhibitors (Atezolizumab plus Bevacizumab) have been tested and approved for the treatment of advanced HCC [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the most common subtype of primary liver malignancy, often accompanied by cirrhosis and chronic hepatitis ( Forner et al, 2018 ; Llovet et al, 2022 ). Despite significant advances in the diagnosis and treatment of liver cancer, long-term survival remains poor ( Laface et al, 2022 ). Because of the hidden origin of liver cancer, many patients are diagnosed at a late stage ( Singal et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine kinase inhibitors (TKIs), such as sorafenib, lenvatinib, and donafenib have improved the clinical efficacy of HCC and prolonged the survival time of patients with advanced HCC. [7][8][9][10] Meanwhile, TACE combined with these anti-angiogenic drugs can reduce the expression level of vascular endothelial growth factor (VEGF), reduce the incidence of tumor recurrence and metastasis, and improve the efficacy of TACE. 11 Regorafenib is an oral multi-kinase inhibitor that blocks a variety of protein kinases related to tumor angiogenesis, cell proliferation, tumor metastasis, and immunity.…”
Section: Introductionmentioning
confidence: 99%